Advance in Nrf2 Signaling Pathway in Leishmaniasis - Sarmistha Saha; Nadezhda Sachivkina; Olga Kuznetsova; Ekaterina Neborak; Natallia Zhabo (Biomedicines)
One of the main components of innate defense against invasive parasites is oxidative stress, which is brought on by reactive oxygen species (ROS). On the other hand, oxidative stressors serve two purposes: free radicals aid in the elimination of pathogens, but they can also set off inflammation, which leads to tissue damage. Nuclear factor erythroid 2-related factor 2 (Nrf2) is a transcription factor that controls the expression of numerous genes involved in the body’s defense against oxidative stress brought on by aging, inflammation, tissue damage, and other pathological consequences. From cutaneous to visceral forms, Leishmania parasites invade macrophages and cause a wide range of human pathologies. Leishmania parasites have a wide range of adaptive mechanisms that disrupt several macrophage functions by altering host signaling pathways. An increasing amount of data are corroborating the idea that one of the primary antioxidant routes to counteract this oxidative burst against parasites is NRF2 signaling, which also interferes with immune responses. The nature and potency of the host immune response, as well as interactions between the invading Leishmania spp., will ascertain the course of infection and the parasites’ eventual survival or eradication. The molecular processes via which Nrf2 coordinates such intricate networks comprising various pathways remain to be completely understood. In light of NRF2’s significant contribution to oxidative stress, we examine the NRF2 antioxidant pathway’s activation mechanism in Leishmania infection in this review. Thus, this review will examine the relationship between Nrf2 signaling and leishmaniasis, as well as explore potential therapeutic strategies for modifying this system.